Analysis of the Role of Tax Consultants in Improving Taxpayer Compliance (Case Study at SHC Manado Tax Consultant Office) - Rambalangi, Yetri Fransiska; Kalangi, Lintje; Weku, Priscillia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The role of tax consultants is instrumental especially in improving taxpayer compliance, especially in the midst of increasingly complex tax regulations. Tax consultants can increase taxpayer awareness of the importance of voluntary tax compliance, which ultimately contributes to increasing state revenue and economic stability. This research aims to analyze the role of tax consultants in improving taxpayer compliance. The method of analysis used in this thesis research is a descriptive method whose purpose is that each data is collected and then analyzed and then a conclusion is drawn and the type of research used is a qualitative descriptive approach. The results showed that the role of tax consultants is very important in helping taxpayers fulfill their tax obligations. Tax consultants play several key roles in assisting taxpayers to improve taxpayer compliance.